Efektivitas Penggunaan Media Peraga Ikonik Jangka Sorong dan Mikrometer Sekrup Terhadap Pemahaman Konsep Pengukuran Siswa - Ropi`i, Nurhasan (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2019)
The limited number of measuring devices generally becomes an obstacle of learning on measurement using Vernier caliper and micrometer screw in class. This situation causes students’ achievement on measurement have not been maximum. Iconic vernier calipers and micrometer screw are needed in the learning as more flexible alternative auxiliary media to increase students’ understanding on measurement concepts. The objective of this research is to determine the increase of students' understanding on the measurement concept after using the vernier calipers and micrometer screw iconic media. The research method used was an experimental method with the design of Pretest-Postest Control Group Design. The research was conducted in class VII of a junior high school in Banjarharjo. The experimental group was class VII A, while the control group is class VII B. The data of students’ understanding on the concept of measurement was taken from the results of the posttest of both groups. The analysis results shows average score of experimental group understanding is 69.58 with 69,44% of individual completeness and 0.51 gain factor. Meanwhile, the average score of control group understanding is 59.72, with 41.67% individual completeness and 0.45 gain factor score. This study indicates that the use of vernier calipers and micrometer screw iconic media is effective in increasing the students’ understanding on measurement concept of students.